'Good order and the police': Policing in the towns and the countryside during Danish absolutism (1660–1800). Issue 1 (1st January 2016) - Mührmann-Lund, Jørgen
Abstract : The emergence of police ordinances and police authorities in the early modern period has traditionally been seen as a way to discipline society in order to increase the power of the absolutist state. However, recent investigations of early modern policing in German and French regions show that 'good order and police' was in demand by the subjects and also adapted to local needs. Inspired by this research this article investigates the enforcement of police ordinances in the Danish market towns of Aalborg and Sæby and the country district of Børglum-Jerslev. The results show that policing remained focused on local needs even after the creation of a royal police office in 1682. Policing mainly concerned the welfare and privileges of burghers in market towns until the introduction of a country police in 1791, when agrarian reforms began to erode the patriarchal order in the countryside. As a new way of governing, 'police' was a way both to govern free burghers and preserve traditional order.